1978
DOI: 10.1007/bf00690438
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis of the central nervous system in the adult. Electron microscopic observations

Abstract: The fine structure and reproductive mechanisms of Toxoplasma gondii are described in a case of toxoplasma encephalitis. Replication was observed in glial cells by an internal budding process: endodyogeny. Distinctive ultrastructural features associated with host cell penetration, and encystation are described. Electron microscopic features previously reported in tissue culture and in experimentally produced infections with T. gondii are confirmed in the human brain tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…They may gain access to the brain and form dormant cysts (Sims et al, 1989;Baragan & Sibley, 2002;Lambert et al, 2006). Proliferating T. gondii tachyzoites have been identified in glial cells and Purkinje cell in human patients who developed toxoplasmosis encephalitis (Powell et al, 1978;Palmer, 2007).…”
Section: Toxoplasma Gondii and Toxoplasmosismentioning
confidence: 99%
“…They may gain access to the brain and form dormant cysts (Sims et al, 1989;Baragan & Sibley, 2002;Lambert et al, 2006). Proliferating T. gondii tachyzoites have been identified in glial cells and Purkinje cell in human patients who developed toxoplasmosis encephalitis (Powell et al, 1978;Palmer, 2007).…”
Section: Toxoplasma Gondii and Toxoplasmosismentioning
confidence: 99%
“…[53][54][55][56] Most studies are in animal models, but a case report of incidental findings at autopsy of an immunocompetent patient indicated a similar pattern in humans. 56 An early study of chronic latent infection in mice (examined at 3, 6, and 12 months post-infection) reported that infected brains appeared normal on gross inspection.…”
mentioning
confidence: 95%
“…In addition, in these keratinocyte host cells, tissue cysts are surrounded by thick keratin filament bundles which consistently obstruct attempts to purify the parasites (25). Close association of intermediate filaments with parasitophorous vacuoles and tissue cysts of T. gondii and N. caninum had also been observed in other host cells (19,44,56).…”
mentioning
confidence: 99%